EFEKTIFITAS PENYULUHAN KESEHATAN TERHADAP PENCEGAHAN STUNTING DI KLINIK MARIANA - Patimah Sari Siregar; Eva Latifah Nurhayati; Kristina L Silalahi (Jurnal Keperawatan Priority, 2021)
Stunting is a chronic nutritional problem in toddlers characterized by a shorter height compared to other children of their age. Children who suffer from Stunting will be more susceptible to disease and as adults are at risk for degenerative diseases. Health counseling is held to increase the knowledge, awareness, willingness, and ability of mothers to continue to provide good nutrition during pregnancy. Knowledge of feeding is from pregnancy to prevent Stunting. Research that focuses on intention, motivation, and knowledge is not sufficient to help mothers overcome obstacles during pregnancy. Besides getting counseling, mothers overcome obstacles during pregnancy. In addition to getting maternal counseling, it requires support, education, and information that is consistent, realistic, and evidence-based to successfully improve nutrition during pregnancy. The goal is to find out the effectiveness of health education on Stunting prevention at the Mariana Clinic. The research will be conducted using a Quasi-Experiment design (quasi-experimental), with the target that pregnant women are given counseling. The methods of data collection are using questionnaires, interviews, and observations. The data analysis method used the dependent t-test, namely the Wilcoxon test. In the paired group, the same subjects were examined before and after the intervention (before and after design) of the questionnaire as a research instrument. The test used is the Wilcoxon test. The results study based on the Wilcoxon test, it was found that the p-value (<0.05) statistically showed that there was the effectiveness of health education on the prevention of Stunting in pregnant women at the Mariana clinic (p-value = 0.002).